Architectural Documentation: A Case Study of Architectural Analysis in Tourism Context of Ancient Ayutthaya Island Area - Tongaroon, Nirandorn (Journal of Architectural/Planning Research and Studies (JARS), 2022)
This research article presents guidelines for developing the process of learning architecture. The method focuses on studying and analyzing the physical characteristics, context, tourist information and architectural developments in buildings related to the tourism industry such as, museums, hotels, restaurants, retails, café, and etc. of Ayutthaya city island and its neighborhood. The learning process are revealed to 4 steps as follows: 1) Study the basic information of Ancient Ayutthaya city island, such as “The image of the city”, tourist behavior, etc. (from lesson and knowledge); 2) The definition of criteria and theme of the case study 3) Study from field trip and site survey by documenting the physical features and architectural dimensions through data storage in various media, such as photographs, architectural drawings; 3) Analyzing architectural concepts and site/ contexts. Then, integrating knowledge from lessons and field trips to the results of “Architectural Documentation”. Moreover, the study process found that there were 4 approaches to designing and promoting the potential of architecture in the context of cultural tourism: 1) Concepts and architectural development patterns in issues related to the potential of the area, context, behavior, building characteristic, and form and space design 2) Guidelines for architectural documentation 3) The identity of Modern Thai Architecture 4) Integration with other fields, such as conservation, renovation or building formed. Finally, it also contributes to the promotion of academic knowledge that will benefit the development of tourism in historical cities and related cultural areas.